Objek Pendidikan dalam Al-Qur’an : Kajian Surat At-Tahrim Ayat 6 - Isyanto, Nur; Idrus, Idrus (Al Ashriyyah, 2021)
Humans are creatures created by Allah SWT who are concrete and most perfect in reason and reasoning, so it is impossible for other creatures who do not have good reasoning to receive Islamic education, which must carry out the Shari'a and fulfill the mandate of Allah SWT as caliph on earth. This article aims to find out the object of education that was the earliest received by humans. This study uses a qualitative approach, provides a basic overview of the topic of discussion, generalizes ideas and develops a tentative theory, opens the possibility for further research on the topic discussed. The analytical method used in this research is descriptive data analysis. The result of this research is that the object of education is the most important and the earliest is the self and then the family, especially the children. Children are a mandate that is entrusted to be educated properly. In fact, a mother must equip herself with knowledge, be willing to continue to learn, and be patient in nurturing and educating her children.